Detecting signatures of a sponge‐associated lifestyle in bacterial genomes. Issue 4 (25th July 2018) - Díez‐Vives, Cristina; Esteves, Ana I. S.; Costa, Rodrigo; Nielsen, Shaun; Thomas, Torsten
Summary: Sponges interact with diverse and rich communities of bacteria that are phylogenetically often distinct from their free‐living counterparts. Recent genomics and metagenomic studies have indicated that bacterial sponge symbionts also have distinct functional features from free‐living bacteria; however, it is unclear, if such genome‐derived functional signatures are common and present in different symbiont taxa. We therefore compared here a large set of genomes from cultured ( Pseudovibrio, Ruegeria and Aquimarina) and yet‐uncultivated ( Synechococcus ) bacteria found in either sponge‐associated or free‐living sources. Our analysis revealed only very few genera‐specific functions that could be correlated with a sponge‐associated lifestyle. Using different sets of sponge‐associated and free‐living bacteria for each genus, we could however show that the functions identified as 'sponge‐associated' are dependent on the reference comparison being made. Using simulation approaches, we show how this influences the robustness of identifying functional signatures and how evolutionary divergence and genomic adaptation can be distinguished. Our results highlight the future need for robust comparative analyses to define genomic signatures of symbiotic lifestyles, whether it is for symbionts of sponges or other host organisms.